PERBANDINGAN KEBERHASILAN TERAPI GLAUKOMA SUDUT TERTUTUP DENGAN GLAUKOMA SUDUT TERBUKA DI RUMAH SAKIT MATA DR. YAP YOGYAKARTA - Dedy Hartanto (FKU 12 UMY, 2012)
Glaucoma is a chronic neuropathy in can be characterized by hollow (cupping) optic disc and reducing the field of view is usually accompanied by an increase in intraocular pressure Primary angle closure glaucoma occurs in eyes with predisposing anatomic abnormalities without the other. Increased intraocular pressure occurs because of blockage of the aqueous outflow due to the occlusion of woven trabekuluar by peripheral iris. This situation can bermanifetasi as an emergency oftamologik or can